Pengembangan Karakter Siswa SDS 118 Muhammadiyah Gunung Tua melalui Pembelajaran PAI Berbasis Nilai-Nilai Islam (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the development of students' character at SD Swasta 118 Muhammadiyah Gunung Tua through Islamic Religious Education (PAI) learning based on Islamic values. Islamic Religious Education plays a strategic role in instilling religious values from an early age, especially at the elementary school level. Through worship habituation strategies, teacher role modeling, contextual learning, and the integration of Islamic values into school culture, students' character can be comprehensively developed encompassing spiritual, moral, and social aspects. This research uses a qualitative descriptive approach with research subjects including the principal, PAI teachers, and students Twenty fifth-grade students from SDS 118 Muhammadiyah Gunung Tua were selected using purposive sampling. This selection technique was applied intentionally, considering that students at this stage are in a transitional period of moral development that greatly requires the internalization of noble moral values. Through a descriptive qualitative approach, the dynamics of student character formation will be explored in depth to determine the extent to which the integration of Islamic values ​​can change their behavior patterns and religious attitudes within the school environment.